Epidemiology of ophthalmia neonatorum: a systematic review and meta-analysis - Randy Asiamah; Gideon Owusu; Pious Tawiah Amoako; Richmond Amponsah; Emmanuel Adator; Samuel Kyei (BMC Pediatrics)
Abstract Purpose To elucidate the global epidemiology of Ophthalmia Neonatorum (ON), as well as its causative organisms and their antibiotic susceptibility patterns. Methods A systematic review of studies reporting the epidemiology of ON was performed using four electronic databases: PubMed, Scopus, Web of Science, and Medline. Data were extracted and study-specific estimates were combined using meta-analysis to obtain pooled proportions. Results A total of 25 studies, which evaluated the epidemiology of ON in 1,117,966 live births, were included in this study. A total of 2,902 cases of ON were identified. The global incidence and prevalence of ON are 2.04% [(95% CI 0.70–5.79%), I 2 = 99.4%] and 7.79% [(95% CI 2.93–19.10%), I 2 = 99.1%], respectively. Staphylococcus spp. (gram-positive) and Serratia marcescens (gram-negative) were the most frequently isolated bacteria associated with the incidence of ON. The pooled resistance of Staphylococcus aureus and Escherichia coli are highest to Penicillin [91.67% (95% CI 87.96–94.31%) and 100.00% (95% CI 0.00–100.00%), respectively], and lowest to Gentamicin [20% (95% CI 15.85–24.91%) and 59.30% (95% CI 52.36–65.89%), respectively]. The pooled resistance of Pseudomonas spp. and Klebsiella spp. to Gentamicin are 50% [(95% CI 43.11 to 56.89%), I 2 = 0.00%] and 50.02% [(95% CI 27.50–72.53%), I 2 = 95.3%], respectively. Conclusion ON is a common ocular morbidity in neonates, especially in those from low-income settings. It is important that all newborns receive adequate preventive care, regardless of their socioeconomic status, in order to reduce the risk of visual impairment and blindness.